La città fra marginalità ed esclusione sociale - Paone, Sonia (SocietàMutamentoPolitica, 2011)
It is not easy to understand the effects on the urban dynamics of the financial crisis began in 2008. The hypothesis that is presented in this paper is that the crisis is acting as an accelerator of some trends of precarization and growing inequality existing in the cities, due to the globalization. In this sense, the examples of the transformations of french banlieues and the dizzy increase of informal settlements in the megacities of the poor areas of the world are considered paradigmatic. The question that remains open concerns the future of the city as a place for social and democratic relations.